The effects of electrode size and discharged power on micro-electro-discharge machining drilling of stainless steel - Gianluca D’Urso; Chiara Ravasio (Advances in Mechanical Engineering, 2016)
This article is about the measurement of actual micro-electro-discharge machining parameters and the statistical analysis of their influence on the process performances. In particular, the discharged power was taken into account as a comprehensive variable able to represent the effect of peak current and voltage on the final result. Thanks to the dedicated signal acquisition system, a correlation among the discharged power and the indexes representing the process parameters was shown. Finally, linear and non-linear regression approaches were implemented in order to obtain predictive equations for the most important aspects of micro-electro-discharge machining, such as the machining time and the electrode wear.